2021
DOI: 10.3389/fphar.2021.700573
|View full text |Cite
|
Sign up to set email alerts
|

New Polyketides With Anti-Inflammatory Activity From the Fungus Aspergillus rugulosa

Abstract: Two new polyketide compounds, asperulosins A and B (1–2), and one new prenylated small molecule, asperulosin C (3), along with nine known compounds (4–12), were isolated and identified from a fungus Aspergillus rugulosa. Their structures were extensively elucidated via HRESIMS, 1D, and 2D NMR analysis. The absolute configurations of the new compounds were determined by the comparison of their electronic circular dichroism (ECD), calculated ECD spectra, and the detailed discussion with those in previous reports… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Six known compounds were identified as methyl anodendroate (5), 31 (R)-(Z,E)-9,11-octadecadien-13-olide (6), 32,33 a patent compound (7), 34 nigrosirpexin F (8), 35 trans-2decenedioic acid (9), 36,37 observed in the blank control (Figure 7). Among them, those treated with compound 9 exhibited the most severe damage with a flattened morphology.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Six known compounds were identified as methyl anodendroate (5), 31 (R)-(Z,E)-9,11-octadecadien-13-olide (6), 32,33 a patent compound (7), 34 nigrosirpexin F (8), 35 trans-2decenedioic acid (9), 36,37 observed in the blank control (Figure 7). Among them, those treated with compound 9 exhibited the most severe damage with a flattened morphology.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The positive control in the assays was dexamethasone, a glucocorticoid drug used for inflammatory relief. Asperulosin A and aspertetronin A were found to possess better or comparable anti-inflammatory effects in comparison to dexamethasone [ 109 ].…”
Section: Fungi With Anti-inflammatory Potentialmentioning
confidence: 99%
“…Several secondary metabolites such as phloroglucinol and glyceollin derived from Aspergillus species have been reported for their anti-inflammatory effect [55,56]. The polyketides isolated from A. rugulosa exhibited anti-inflammatory effects better than the positive control [57]. Similarly, a review of Aspergillus genus metabolites revealed that a rich source of anti-inflammatory metabolites are synthesized by Aspergillus genus species such as, polyketides, terpenoids, butenolides, and alkaloids [58].…”
Section: Table 5 Anti-inflammatory Activity Of Ethyl Acetate Extract ...mentioning
confidence: 99%